Analysis of the Causes of Discrepancy of Stock Taking of Spare Parts in Spare Parts Warehouses Using the Dmaic Method - Irawan, Dwi; Jayadih, Epan; Elfirawati, Putri Arwen; Agustin, Tyna Kurniati Noer; Andika, Wazri Himawansyah Putra; Prastyo, Yudi (Lentera Ilmu Nusantara, 2024)
PT XYZ, a manufacturing company specializing in scanners and printers, experienced a significant discrepancy between the actual part count and the system data during its 2024 stock opname. A root cause analyze using the DMAIC methodology identified errors in the returned parts process from production as the primary issue. This discrepancy resulted in a substantial financial loss of Rp.271,810,000. By implementing more effective work instructions and standard operating procedures, the discrepancy was reduced by (Rp.176.094.963), resulting in cost savings of (Rp.95.715.037) for the company.